Effects of Land Use/Cover and Meteorological Changes on Regional Climate under Different SSP-RCP Scenarios: A Case Study in Zhengzhou, China - Tianqi Bai; Like Fan; Genxin Song; Hongquan Song; Xutong Ru; Yaobin Wang; Haopeng Zhang; Ruiqi Min; Weijiao Wang (Remote Sensing, 2023)
To better understand the possible role of projected land use and cover change (LUCC) in future regional climate projections, we explored the regional climate change response from land use/cover change under different climate scenarios. To do so, we propose a research framework based on different SSP-RCPs to simulate and explore the impacts of future land use/cover changes on the future climate of Zhengzhou City, China, using the Weather Research and Forecasting (WRF) model with land use/cover and meteorological data under different SSP-RCP scenarios based on CMIP6. Two scenarios, SSP2-4.5 and SSP5-8.5, were compared and analyzed by simulating changes in future climate factors of temperature at 2 m height above ground(T2) and precipitation. The results show that T2 is higher for all 4 months by the year 2060 compared to that in the year 2030. Furthermore, a comparison of the abovementioned years showed that the mean temperatures of January and July were higher than those of SSP2-4.5 under the SSP5-8.5 scenario in both years, but in 2030, the mean T2 of April and October were lower than those of SSP2-4.5 under the SSP5-8.5 scenario. In terms of precipitation, both scenarios have no significant precipitation in July in 2030 and 2060, but there is an unusual increase in January and October.